Looking for biological factors to predict the risk of active cytomegalovirus infection in non‐immunosuppressed critically ill patients. Issue 5 (5th November 2013) - Bravo, Dayana; Clari, María A.; Aguilar, Gerardo; Belda, Javier; Giménez, Estela; Carbonell, José A.; Henao, Liliana; Navarro, David
ABSTRACT The identification of non‐immunosuppressed critically ill patients most at risk for developing cytomegalovirus (CMV) reactivation is potentially of great clinical relevance. The current study was aimed at determining (i) whether single nucleotide polymorphisms in the genes coding for chemokine receptor 5 (CCR5), interleukin‐10 IL‐10), and monocyte chemoattractant protein‐1 (MCP‐1) have an impact on the incidence rate of active CMV infection, (ii) whether serum levels of CMV‐specific IgGs are associated with the risk of CMV reactivation, and (iii) whether detection of CMV DNA in saliva precedes that in the lower respiratory tract or the blood compartment. A total of 36 out of 78 patients (46%) developed an episode of active CMV infection. The incidence rate of active CMV infection was not significantly associated with any single nucleotide polymorphisms. A trend towards a lower incidence of active CMV infection (P = 0.06) was noted in patients harboring the IL10 C/C genotype. Patients carrying the CCR5 A/A genotype had high CMV DNA loads in tracheal aspirates. The serum levels of CMV IgGs did not differ significantly between patients with a subsequent episode of active CMV infection (median, 217 IU/mL) or without one (median, 494 IU/mL). Detection of CMV DNA in saliva did not usually precede that in plasma and/or tracheal aspirates. In summary, the analysis of single nucleotide polymorphisms in the IL10 and CCR5 genes might help to determine the risk of active CMV infection or the level of CMV replication within episodes, respectively, in non‐immunosuppressed critically ill patients. J. Med. Virol. 86:827–833, 2014. © 2013 Wiley Periodicals, Inc.